Blockade of TLR2 and TLR4 Attenuates Inflammatory Response and Parasite Load in Cutaneous Leishmaniasis - Carneiro, Pedro Paulo; Dórea, Andreza S.; Oliveira, Walker N.; Guimarães, Luiz Henrique; Brodskyn, Claúdia; Carvalho, Edgar M.; Bacellar, Olívia (Frontiers in Immunology, 2021)
Human cutaneous leishmaniasis (CL) caused by Leishmania braziliensis is characterized by a pronounced inflammatory response associated with ulcer development. Monocytes/macrophages, the main cells harboring parasites, are largely responsible for parasite control. Toll-like receptor (TLR) signaling leads to the transcription of inflammatory mediators, such as IL-1β and TNF during innate immune response. TLR antagonists have been used in the treatment of inflammatory disease. The neutralization of these receptors may attenuate an exacerbated inflammatory response. We evaluated the ability of TLR2 and TLR4 antagonists to modulate host immune response in L. braziliensis-infected monocytes and cells from CL patient skin lesions. Following TLR2 and TLR4 neutralization, decreased numbers of infected cells and internalized parasites were detected in CL patient monocytes. In addition, reductions in oxidative burst, IL-1β, TNF and CXCL9 production were observed. TNF production by cells from CL lesions also decreased after TLR2 and TLR4 neutralization. The attenuation of host inflammatory response after neutralizing these receptors suggests the potential of TLR antagonists as immunomodulators in association with antimonial therapy in human cutaneous leishmaniasis.